(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Scheduled caste refers to caste falling in the scheduled category. Caste acquired a new meaning in India after Independence. With the introduction of reservation policy in 1950, a large number of caste groups were assigned the status of scheduled castes, done on the basis of a scheduling policy which has been evolving since 1950. The list of scheduled castes for various states and union territories notified under the provision of the Indian Constitution (Article 341) or supplemented from time to time. Scheduled caste, as defined by the Constitution in 1950, included all the people covered under the category of Sudras and other castes that too had suffered similar neglect in the past and had remained backward.